Safety of Sofosbuvir and Ribavirin Combination Therapy in a Patient Who Developed Anemia due to Ribavirin - Hirokazu Suii; Itaru Ozeki; Ryoji Tatsumi; Masakatsu Yamaguchi; Mutsuumi Kimura; Tomohiro Arakawa; Tomoaki Nakajima; Yasuaki Kuwata; Takumi Ohmura; Shuhei Hige; Yoshiyasu Karino; Joji Toyota (Case Reports in Hepatology)
Interferon (IFN) and ribavirin (RBV) combination therapy was previously the standard of care for treatment of hepatitis C virus (HCV) genotype 2 infection. But, it often induced hemolytic anemia. In 2014, sofosbuvir (SOF) was approved for the treatment of chronic HCV genotype 2 in Japan. SOF/RBV therapy is more effective against genotype 2 than IFN/RBV therapy. We report a case of a 74-year-old woman with chronic HCV genotype 2b infection. She received five treatments including RBV and IFN therapy before SOF was approved and all of them were ineffective. Therapies that included RBV induced severe anemia and led to discontinuation of treatment. With pegylated IFN/RBV therapy, the maximum change in hemoglobin (Hb) from baseline was −3.7 g/dL. However, SOF/RBV therapy was effective and she achieved sustained virologic response (SVR) with a maximum change in Hb from baseline of only −1.2 g/dL. We also found reticulocyte count was very low during treatment in this case and speculate it was one of the reasons that she developed hemolytic anemia with RBV. In conclusion, SOF/RBV therapy is effective and allowed the patient to achieve SVR. An SOF/RBV regimen is safe and effective for patients who have or are at risk of anemia induced by RBV.